Renewal of Islamic Religious Education Thematic Learning Approaches in the Digital Age - Novianto, Erik; Hidayat, Nur (Institut Agama Islam Sunan Giri Ponorogo, 2023)
This study aims to provide an overview or offer thematic learning designs of Islamic religious education using scientific theories and principles of digital era education. This research method uses a qualitative approach to library research (library research). Following the topics discussed, the researcher categorizes data sources into primary data sources studied from library sources on PAI thematic education and library sources on digital era education. Secondary data sources include supporting data from library materials relevant to the discussion, books, theses, dissertations, journal articles, etc. Data collection techniques used observation and documentation techniques; finally, for data analysis techniques, researchers used content analysis techniques, inductive analysis, deductive analysis, descriptive analysis, and interpretive analysis. The study results show that with PAI thematic learning designs based on digital era education, you can obtain planning patterns that align with the theories and principles of digital era education. Both are seen from the learning communication approach, learning approach methods, and learning strategies. Second, the PAI thematic learning implementation pattern can be implemented by integrating e-learning platforms from social media, video conferencing, learning videos, digital literacy media, and media submit assignments. Finally, the PAI thematic learning evaluation system may use various websites, including Google Forms, Quizlet, and Classroom.